Generation of Infectious Mimivirus Virions Through Inoculation of Viral DNA Within Acanthamoeba castellanii Shows Involvement of Five Proteins, Essentially Uncharacterized - Sahmi-Bounsiar, Dehia; Baudoin, Jean-Pierre; Hannat, Sihem; Decloquement, Philippe; Chabrieres, Eric; Aherfi, Sarah; La Scola, Bernard (Frontiers in Microbiology, 2021)
One of the most curious findings associated with the discovery of Acanthamoena polyphaga mimivirus (APMV) was the presence of many proteins and RNAs within the virion. Although some hypotheses on their role in Acanthamoeba infection have been put forward, none have been validated. In this study we directly transfected mimivirus DNA with or without additional proteinase K treatment to extracted DNA into A. castellanii. In this way it was possible to generate infectious APMV virions but only without extra proteinase K treatment of extracted DNA. Virus genomes before and after transfection were identical. We searched for the remaining DNA-associated proteins that were digested by proteinase K and could visualise at least 5 putative proteins. MALDI-TOF and LC-MS comparison with protein databases allowed identification of four hypothetical proteins, L442, L724, L829, R387 and putative GMC-type oxidoreductase R135. We believe that L442 play the major role in this protein-DNA interaction. In the future, expression in vectors and then diffraction of X-rays by protein crystals could help reveal the exact structure of this protein and its precise role.